Epidemiology and preventive strategies of monkey pox virus with emphasis in Delta State, Nigeria - Ogor, Kingsley Ijeoma; Nwose, Ezekiel Uba; Moyegbone, John Esimaje; Abdulahi, Zullaihat Muhammad (International Journal of Research in Medical Sciences, 2025)
Monkey pox is an emerging and re-emerging viral zoonotic infection occurring in different part of the globe with the potential of assuming a public health emergency of international concern. Deforestation and human intrusion into the habitats of the monkey pox animal hosts were suggested as probable causes of monkey pox outbreaks. Review of previous literatures were done using google scholar, Mendeley reference library, and Pubmed search engines. The key words used includes; monkey pox, epidemiology of monkey pox, Mpox and reservoirs of Monkey pox. Monkey pox virus was first isolated from Cynomolgus macaques in 1958 and also in a nine months old baby in the Democratic Republic of Congo in 1970. In 2020, there were more than 6300-suspected cases of monkey pox infection, of which 95% were in the Democratic Republic of the Congo. From January 1, through August 7, 2022, a total of 27, 814 laboratory confirmed cases of monkey pox and 11 deaths were reported to WHO from 89 countries. From 2017 to 2022, there were 249 confirmed cases across Nigeria, with a notable resurgence in recent years. In June 2022 alone, there were 23 confirmed cases and one death. The monkey pox virus can spread from human to human as well as from animal to human. The most effective way to prevent viral zoonosis is to maintain the barriers between natural reservoirs and human society, in mind of the “one health” concept.